Expert car care system - Camacho, Adler Mari A. (Animo Repository, 1993)
The ECCS (Expert Car Care System) is a consultation program developed not to replace mechanics, but simply to aid in the diagnosis of automotive engine malfunctions. Its users will not be restricted to mechanics as automobile owners can also avail of the system given its easy to use features. These include graphical screen displays and the use of pointing devices which make utilization of the system faster and easier. It also provides its users with repair and maintenance procedures to be performed in correlation to the needs of the vehicle. A glossary facility is included to provide its users with a means of procuring the definitions of terms regarding the automobile. Furthermore, the system's user will not be limited to simply interrogating the system. Its updating facilities allow the addition of information preventing the system's different storage of information from becoming outdated.